iPSC-derived exosomes as amphotericin B carriers: a promising approach to combat cryptococcal meningitis - Zhao, Jingyu; Fang, Wei; Gao, Yangjie; Chen, Jiquan; Wang, Guizhen; Gu, Julin (Frontiers in Microbiology, 2025)
BackgroundCryptococcal meningitis (CM) is a significant global health issue, particularly affecting individuals with HIV. Amphotericin B (AmB) serves as the cornerstone treatment for CM; however, its clinical application is restricted due to limited penetration of the blood–brain barrier and associated nephrotoxicity.ObjectiveThis study investigates the use of exosomes derived from induced pluripotent stem cells (iPSC-Exos) as carriers for AmB in treating CM, aiming to enhance therapeutic efficacy and safety and reduce AmB toxicity.MethodsExosomes were extracted from iPSC culture supernatants using ultrafiltration and ultracentrifugation. Their morphology and size were analyzed using transmission electron microscopy (TEM) and nanoparticle flow cytometry (nFCM). Purity was confirmed by Western blotting for markers CD9, CD63, and TSG101. AmB was loaded into iPSC-Exos using a co-incubation method. The cytotoxicity of the iPSC-Exo/AmB complex was evaluated on HEK 293 T and RAW264.7 cells using the CCK-8 assay, while apoptosis was assessed using live/dead cell staining and flow cytometry. The hemolytic effects were tested using rabbit red blood cells. In a C57BL/6 J mouse model of cryptococcal infection, treatment groups (AmB, iPSC-Exo/AmB, and iPSC-Exo) were administered corresponding drugs, with blood and brain samples collected for analysis. The minimum inhibitory concentration (MIC) of iPSC-Exo/AmB and conventional AmB against Cryptococcus was determined.ResultsThe iPSC-Exo/AmB complex exhibited reduced cytotoxicity in vitro and decreased AmB-induced renal and hepatic toxicity in vivo. Its MIC against Cryptococcus was over eight times lower than conventional AmB, significantly reducing fungal burden in the mouse brain and lowering serum inflammatory factors.ConclusionThe iPSC-Exo/AmB complex is a promising therapeutic strategy that enhances AmB efficacy while reducing toxicity, offering new hope for treating CM and other refractory fungal infections of the central nervous system.